PEMANFAATAN CANGKANG KELAPA SAWIT SEBAGAI BIOBRIKET: ANALISIS POTENSI ENERGI TERBARUKAN - Delianti; Choerullah, Andy; utami, Rizka; Fadhilah, Alvi Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasing global energy demand and the depletion of fossil fuel resources have driven the development of environmentally friendly renewable energy sources. Biomass, particularly oil palm shell waste, represents a promising alternative energy source due to its abundant availability in Indonesia. This study aims to analyze the potential utilization of oil palm shells as raw materials for bio-briquettes and to evaluate the factors influencing calorific value as a key parameter of fuel quality. The method employed is a literature review of previous studies on bio-briquette production using oil palm shells with variations in raw material composition, binder content, and carbonization conditions. The results indicate that the calorific value of bio-briquettes ranges from 3816 to 7209 cal/g, with most values meeting the Indonesian National Standard (SNI >5000 cal/g). The main factors affecting calorific value include raw material composition, binder proportion, and carbonization temperature. Lower binder content and optimal carbonization temperature significantly enhance the quality of the bio-briquettes. Therefore, oil palm shells demonstrate strong potential as a renewable energy source in the form of efficient and environmentally friendly bio-briquettes.